Penurunan Distres Psikologi Remaja dengan Penyakit Kronis melalui Peer Group Support: Scoping Review - Cahyaningrum, Devy Novita; Nurachmah, Elly; Gayatri, Dewi (Universitas Faletehan, 2025)
Adolescents with chronic illnesses are at high risk of psychological distress such as stress, anxiety and depression that can affect their overall quality of life. One of effective approaches to reduce these impacts is peer group support. This study was to examine the effects of peer group support intervention in reducing psychological distress in adolescents with chronic illness through scoping review. The articles were obtained from SpringerLink, Science Direct, Taylor & Francis, Proquest, Scopus, BMC, and PubMed databases. Article selection was done by the PRISMA-ScR method. Searches of 7 databases obtained 1,578 articles. Based on the inclusion criteria, 291 articles were eligible. Further screening based on title, abstract, and full text selected 10 articles for analysis. Furthermore, the quality of the article was assessed using Jonna Briggs Institute (JBI). The results showed that peer group support reduced stress, anxiety, depression, and increased social support and emotional well-being. Interventions that emphasized active communication among adolescents have a positive impact on psychological disorders. Peer group support can reduce psychological distress in adolescents with chronic illness. This approach also strengthens positive social relationships among adolescents. Further research is needed to explore the factors that influence the success of this intervention and develop more adaptive support models.